1981
DOI: 10.1152/jappl.1981.51.6.1388
|View full text |Cite
|
Sign up to set email alerts
|

Decay of inspiratory muscle activity in chronic airway obstruction

Abstract: Relative decay rate of inspiratory muscle electrical activity (RDRI) in patients with chronic airway obstruction increased with decreasing expiratory time (TE), being faster than in normal subjects for a given TE. Time course of decay was similar in shape to that of normal subjects, whereas persistence time of activity during expiration was about half. Hence, braking action of inspiratory muscles in patients was smaller than in normal subjects. No tonic activity of inspiratory muscles was found in patients, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 0 publications
0
32
0
2
Order By: Relevance
“…In patients with airflow obstruction, there is evidence that inspiratory and expiratory muscles are relaxed throughout much of expiration [11,15]. In normal subjects, evidence points to full relaxation only occurring towards the end of expiration, inspiratory muscle activity continuing well This study shows that there is a relationship between these measurements made from analysis of tidal breathing and recognized measurements of airflow obstruction and overinflation.…”
Section: Analysis Of Expiratory Tidal Flow Patterns As a Diagnostic Tmentioning
confidence: 60%
See 1 more Smart Citation
“…In patients with airflow obstruction, there is evidence that inspiratory and expiratory muscles are relaxed throughout much of expiration [11,15]. In normal subjects, evidence points to full relaxation only occurring towards the end of expiration, inspiratory muscle activity continuing well This study shows that there is a relationship between these measurements made from analysis of tidal breathing and recognized measurements of airflow obstruction and overinflation.…”
Section: Analysis Of Expiratory Tidal Flow Patterns As a Diagnostic Tmentioning
confidence: 60%
“…This slope is the time constant of relaxed expiration and by analogy with an electrical model Trs is equal to resistance×compliance of the total respiratory system (lungs+ chest wall). COMROE et al [14] suggested that volume-flow curves of passive expiration could be used to assess the mechanical properties of the lung and chest wall.In patients with airflow obstruction, there is evidence that inspiratory and expiratory muscles are relaxed throughout much of expiration [11,15]. In normal subjects, evidence points to full relaxation only occurring towards the end of expiration, inspiratory muscle activity continuing well This study shows that there is a relationship between these measurements made from analysis of tidal breathing and recognized measurements of airflow obstruction and overinflation.…”
mentioning
confidence: 60%
“…In obstructed airways, peak expiratory flow is reached sooner than in those with normal airways. This more rapid rise in expiratory flow is thought to be due to a faster decline in post-inspiratory muscle activity [7,8]. As a consequence, a greater part of expiration is passive in subjects with airway obstruction.…”
mentioning
confidence: 99%
“…In COPD, electrophysiological studies suggest that the inspiratory muscles "switch off" early in expiration [13,14], but in asthma it appears that tonic inspiratory muscle activity may remain throughout expiration and this may contribute to the hyperinflation, at least when asthma is induced acutely, e.g. with histamine or methacholine.…”
Section: Mechanisms Of Hyperinflationmentioning
confidence: 99%